Mitochondria-Targeted Triphenylphosphonium-Hydroxytyrosol Prevents Lipotoxicity-Induced Endothelial Injury by Enhancing Mitochondrial Function and Redox Balance via Promoting FoxO1 and Nrf2 Nuclear Translocation and Suppressing Inflammation via Inhibiting p38/NF-кB Pathway - Xuyun Liu; Jing Gao; Yizhen Yan; Eleftheria A. Georgiou; Jing Lou; Mengya Feng; Xing Zhang; Feng Gao; Jiankang Liu; Ioannis K. Kostakis; Lin Zhao (MDPI AG, 2023)
Hyperlipidemia results in endothelial dysfunction, which is intimately associated with disturbed mitochondrial homeostasis, and is a real risk factor for cardiovascular diseases (CVDs). Triphenylphosphonium (TPP+)-HT, constructed by linking a mitochondrial-targeting moiety TPP+ to hydroxytyrosol (HT), enters the cell and accumulates in mitochondria and is thus an important candidate drug for preventing hyperlipidemia-induced endothelial injury. In the present study, we found that TPP-HT has a better anti-inflammatory effect than HT. In vivo, TPP-HT significantly prevented hyperlipidemia-induced adverse changes in the serological lipid panel, as well as endothelial and mitochondrial dysfunction of the thoracic aorta. Similarly, in vitro, TPP-HT exhibited similar protective effects in palmitate (PA)-induced endothelial dysfunction, particularly enhanced expression of the mitochondrial ETC complex II, recovered FoxO1 expression in PA-injured human aorta endothelial cells (HAECs) and promoted FoxO1 nuclear translocation. We further demonstrated that FoxO1 plays a pivotal role in regulating ATP production in the presence of TPP-HT by using the siFoxO1 knockdown technique. Simultaneously, TPP-HT enhanced Nrf2 nuclear translocation, consistent with the in vivo findings of immunofluorescence, and the antioxidant effect of TPP-HT was almost entirely blocked by siNrf2. Concomitantly, TPP-HT's anti-inflammatory effects in the current study were primarily mediated via the p38 MAPK/NF-κB signaling pathway in addition to the FoxO1 and Nrf2 pathways. In brief, our findings suggest that mitochondria-targeted TPP-HT prevents lipotoxicity induced endothelial dysfunction by enhancing mitochondrial function and redox balance by promoting FoxO1 and Nrf2 nuclear translocation.